Chitosan-titanium dioxide (Cs-Tio2) catalyst synthesized on glass substrate for photodegradation / Muhammad Nur Iman Amir - Muhammad Nur Iman, Amir (2016)

(untitled)
Methyl orange (MO) is one of the azo compounds that is present in the wastewater mainly from the textile industry. MO is also capable of producing a secondary waste product, which might become a major pollutant towards the environment and aquatic organisms. With that in mind, research is focused to look into photodegradation methods based on the advance oxidation process by Titanium Dioxide (TiO2) semiconductor, which offers a more effective and highly selective degradation process at minimal consumption of energy and costs. However, nanosized of TiO2 catalyst are limited by factors such as dispersion, separation, and adsorption. In this study, Chitosan (Cs) biopolymer is incorporated into TiO2 nanoparticles as a support and adsorption site, forming an effective photocatalyst system. It is expected that the -OH and -NH2 functional groups of Cs would act as active sites, creating excellent interfaces that would attract MO molecules. Meanwhile, the porous structure of Cs helps adsorb the MO molecules. The stability and separation ability of the Cs-TiO2 photocatalysts system improved as it is further immobilized on the surface of the glass substrate. TiO2 was first synthesized using the sol-gel method (TiO2(SY)), and its phase, particle size, morphology, band gap, and chemical structure are analyzed and compared to that of TiO2-Commercial Degussa P25 (TiO2(DP25)). Then, TiO2 nanoparticles (both TiO2(SY) and TiO2(DP25)) were incorporated with Cs solution before being immobilized on glass plates via the dip-coating technique. The surface interactions and the band gap of Cs-TiO2/Glass photocatalyst was determined using techniques such as FESEM+EDS, FTIR, and UV-DR analysis, respectively. The photocatalytic activity of both photocatalysts (Cs-TiO2(DP25)/Glass and Cs-TiO2(SY)/Glass) was demonstrated on the simulated MO solution (10 ppm) irradiated under UV-light (6 W, λ=312 nm and 365 nm). UV-Vis analysis was conducted to analyze the influence of adsorption–photodegradation of MO using different photodegradation parameters. The results reported that the anatase phase, with a particle size of less than 50 nm and v homogenous spherical features of TiO2, was successfully produced through the sol-gel method. The Cs-TiO2/Glass photocatalyst exhibited excellent formation of coordinate covalent bonding between Ti-O to Si-O, Ti-O-to-NH2, or Ti-O-to-OH groups. The photocatalytic activities of TiO2 exhibited a promising increment with better adsorptions under different photocatalytic conditions, including the concentration and pH of MO, photocatalysts cycles and the weight ratio of the surface of the glass substrate. The optimum photodegradation recorded for the Cs-TiO2/Glass for TiO2(SY) and TiO2(DP25) reached 80%, with 10 ppm of MO concentration, at a normal pH and 1 hour of retention time. Meanwhile, the optimum adsorption process that was recorded for that photocatalyst is expected to exceed 70%. It was concluded that the combination of the adsorption and catalytic photodegradation process from Cs-TiO2/Glass photocatalyst has great potential for treating wastewater for other types of organic/inorganic pollutants.